Growth hormone on ovarian morphology of lambaris (Astyanax bimaculatus) after induced spawning - Marcon,Lucas (2019)
ABSTRACT: Lambari, Astyanax bimaculatus, is an oviparous, multiple-spawning fish that is reproductively active throughout the year, which makes it promising for cultivation and research. This research histologically evaluates the ovaries of lambari that have undergone artificial spawning induced with pituitary extract (control group), and the effect of growth hormone at a dose of 2 mg/g body weight (treatment group) on the subsequent process of ovarian recovery. Ovaries of fish in both the control and treatments groups were collected at 120 hours after spawning and analyzed using optical microscopy to characterize the average quantities of: follicles in different stages of development, post-ovulatory follicles, follicular atresia and granulocytes. Quantity and morphology of early and advanced primary follicles did not differ between the treatment and control groups; an important and necessary factor for ovarian recovery for subsequent spawning. There was a greater amount of granulocytes in initial atresia in the group treated with growth hormone. These results demonstrated that the administration of growth hormone may potentiate the process of ovarian recovery after induced spawning.